Asymptotic analysis of multi‐branch EGC and SC over equally correlated Rician channels. Issue 5 (27th May 2013) - Liu, Shuo; Song, Xuegui; Cheng, Julian; Beaulieu, Norman C.
ABSTRACT Closed‐form asymptotic expressions for bit error rate and outage probability are derived for multi‐branch equal gain combining and selection combining receiver diversity over equally correlated Rician channels. Numerical results indicate that these analytical solutions can provide accurate estimation of bit error rate and outage probability in large signal‐to‐noise ratio regimes. The analytical results reveal some important insights into the performance characteristics of equal gain combining and selection combining diversity operating over equally correlated Rician fading channels. Copyright © 2013 John Wiley & Sons, Ltd.